Beyond glycemic control: molecular mechanisms of metformin in modulating cytokine networks in polycystic ovary syndrome - Ullah, Amin; Chen, Yongxiu; Zhang, Fan; Shen, Bairong (Frontiers in Endocrinology, 2026)
Polycystic ovary syndrome (PCOS) is a well-known hormonal and metabolic condition linked to immune system irregularities and persistent inflammatory responses. Cytokines play a central role in PCOS, contributing to insulin resistance (IR), ovarian dysfunction, and systemic inflammation. Metformin (Met), a first-line treatment for IR, exhibits immunomodulatory properties beyond its glucose-lowering effects. This review critically evaluates the molecular mechanisms by which Met modulates pro- and anti-inflammatory cytokines in PCOS, synthesizing preclinical and clinical evidence while highlighting inconsistencies and therapeutic implications. Met suppresses inflammation by reducing pro-inflammatory cytokines such as IL-6, IL-1, IL-17, TNF-α, and others. Met also regulates TGF-β signaling, mitigating ovarian fibrosis while promoting follicular development and oocyte maturation through increased expression of TGF-β family members such as GDF-9 and BMP-15. These effects highlight Met’s dual role in modulating inflammation and fibrosis. Additionally, Met influences inflammatory chemokines such as CXCL13, fractalkine, and others, further regulating immune responses and reducing inflammation. Moreover, combining Met with anti-inflammatory agents, such as resveratrol and probiotics, shows synergistic benefits in PCOS management. Understanding Met’s immunomodulatory mechanisms offers new insights into its therapeutic potential beyond glucose metabolism. Future large-scale, phenotype-stratified clinical trials are warranted to validate these mechanisms and translate the immunomodulatory potential of metformin into tailored therapeutic strategies for PCOS.